Avaliação do desempenho da alocação de recursos públicos na atenção básica da saúde pública brasileira - Lucas Maia dos Santos (2011)
This study was carried out to evaluate the performance of resources allocation in primary health care of southeastern Brazilian municipalities, from 2007 to 2010. The following question was answered: a) what the relative efficiency of the municipalities of southeastern Brazilian municipalities of resources allocation in primary health care? Which municipalities are benchmarks in allocating these resources? Was there any change in productivity in this resource allocation over the years from 2007 to 2010, since the beginning of the National Primary Care Policy? Thus, it was examined a nonprobabilistic sample by convenience of 1097 municipalities of southeastern Brazil, from government and research institutes databases. For the approach to the problem and operationalization of variables, the research was primarily quantitative in the survey, tabulating and data analysis. After descriptive analysis, we performed a cluster analysis considering the dimensions of poverty, development, private coverage and size of the municipality. Then, for each cluster were calculated the efficiency scores, using the method of Data Envelopment Analysis (DEA), with orientation for increasing the products. In the model of efficiency, the variables considered as inputs were the number of Family Health Teams and number of establishments. As outputs were used the number of people registered by the Family Health Teams, the number of home visits by the Family Health Teams and number of production in primary health care. Finally, we analyzed the change in the productivity of each group of municipalities by Malmquist index. Among the main results, we observed the presence of four distinct groups of municipalities and analysis of the efficiency showed disparities in the rate calculated. Besides, the benchmarks and the targets of increasing the supply of services in primary health care were highlighted for each of the groups to achieve the efficient production frontier. The reduction in productivity was observed for almost all years analyzed in the four groups. Moreover, it was found changes in all groups in the production frontier and the pure technical efficiency scores. The great disparity in the efficiency scores obtained may be related to the autonomy of municipalities that do not allocate resources equally. Thus, this study addresses the concepts of performance analysis highlighted by literature, contributing to accountability in the public sector